2009
DOI: 10.1111/j.1365-2230.2009.03209.x
|View full text |Cite
|
Sign up to set email alerts
|

Periungual lesions in pyoderma gangrenosum

Abstract: Pyoderma gangrenosum (PG) is a progressive cutaneous necrosis of unknown origin. We report a case of PG presenting with periungual lesions. A 57-year-old woman was on treatment with ciclosporin A for PG. During tapering of the ciclosporin A dose, proliferating periungual lesions developed on the third and fourth finger of the left hand, the fourth finger of the right hand, and on the right great toe and the left fifth toe. All lesions appeared within a 4-week period. These abnormalities were ulcerated, involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…In the literature review presented, a prominent rate of gastrointestinal (38.9%) and hematologic abnormalities (44.4%) was evident. References (all studies reported one patient with hand and finger involvement, except for Huish et al, 5 which reported a series of seven patients): Lucchina et al, 20 Reich et al, 21 Ghosn et al, 12 Zivanovic et al, 10 Mujadzic et al, 22 Weenig et al, 23 Greidanus and Honl, 7 Grange et al, 14 Youker et al, 9 Braun-Falco et al, 24 Manthey and Schissel, 5 Bennett et al, 4,6 Nurre et al, 26 Worley et al, 27 Adam et al, 28 Kitagawa et al, 29 Laurencin and Shoen, 30 Nihei et al, 31 Brown et al, 13 Gasparini et al, 32 Papilion and Bergfield, 33 Young et al, 34 Kanel et al, 35 Schwarz et al, 36 Griffiths and Sundaram, 37 Yusef and Ead, 38 By the time patients present for care of their lesions and analgesics, the red plaques and pustules have already rapidly evolved. On examination, an ulcer with necrosis of a mucopurulent base can be seen with violaceous raised borders.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review presented, a prominent rate of gastrointestinal (38.9%) and hematologic abnormalities (44.4%) was evident. References (all studies reported one patient with hand and finger involvement, except for Huish et al, 5 which reported a series of seven patients): Lucchina et al, 20 Reich et al, 21 Ghosn et al, 12 Zivanovic et al, 10 Mujadzic et al, 22 Weenig et al, 23 Greidanus and Honl, 7 Grange et al, 14 Youker et al, 9 Braun-Falco et al, 24 Manthey and Schissel, 5 Bennett et al, 4,6 Nurre et al, 26 Worley et al, 27 Adam et al, 28 Kitagawa et al, 29 Laurencin and Shoen, 30 Nihei et al, 31 Brown et al, 13 Gasparini et al, 32 Papilion and Bergfield, 33 Young et al, 34 Kanel et al, 35 Schwarz et al, 36 Griffiths and Sundaram, 37 Yusef and Ead, 38 By the time patients present for care of their lesions and analgesics, the red plaques and pustules have already rapidly evolved. On examination, an ulcer with necrosis of a mucopurulent base can be seen with violaceous raised borders.…”
Section: Discussionmentioning
confidence: 99%
“…A case of periungual pyoderma gangrenosum was published by Reich et al 76 in 2009 with worsening noted at a dose of cyclosporine 1.5 mg/kg/day as monotherapy. The lesion improved within 6 weeks with an increase in the dose to 5 mg/kg/day and resolved after 6 months of treatment.…”
Section: Pyoderma Gangrenosummentioning
confidence: 95%
“…Ciclosporin has been prescribed and elsewhere in the U.K. (both within and outside its licence) for the dermatological conditions listed in Table …”
Section: Unlicensed Indicationsmentioning
confidence: 99%